Why should Business schools teach blockchain technology? The case of Botswana Accountancy College - Mutoko, Wilbert R.; Gande, Tapiwa (European Scientific Journal, ESJ, 2021)
In this digital era, tertiary education institutions students need to be acquainted with the latest technology such as blockchain, to equip them for industry readiness. There is a paradigm shift in blockchain technology. Thus, business schools would do well to teach tertiary students about blockchain technology which in turn can help them to solve real-life and industry challenges efficiently and effectively. This paper aimed to investigate tertiary students’ awareness and competency of blockchain technology and cryptocurrency. The paper’s objectives were to assess students’ level of knowledge on blockchain, to explore students’ depth of awareness and competency on bitcoin and altcoins, and to recommend steps that business schools can take to teach students on blockchain. In July 2018, a closed-ended questionnaire was distributed to 266 students studying Business and Leisure related programs at Botswana Accountancy College, School of Business & Leisure. Quota-randomized system was used to allow participation of respondents that are more entrepreneurially aligned according to course content and aims. The data was analyzed using Statistical Package for Social Sciences (SPSS). The study findings revealed that most students are challenged or know little about blockchain, let alone Bitcoin and Altcoins. Thus, business schools should take it upon themselves to educate not only students, but the community at large about blockchain to bring awareness. Furthermore, business schools such as BAC should make policies that allow them to embed blockchain technology into their teaching/learning strategies, record-keeping, and information management.